STRATEGI RRI.CO.ID YOGYAKARTA DALAM UPAYA MEMBANGUN CITRA POSITIF DI YOGYAKARTA DI TENGAH ISU KLITIH - Bima Kramawijaya; Zahrotus Sa'idah (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2023)
This research analyzes the agenda-setting strategies employed by the news portal rri.co.id in building a positive image of Yogyakarta City regarding the phenomenon of